Examining connections among seed system, nutrition and gender in Vietnam - Consignado, Ysabel Anne Lee; Nabuuma, Deborah; Swaans, Cornelis (Bioversity International and the International Center for Tropical Agriculture, 2022)
A blog about the importance and opportunity to evaluate the gender and empowerment within a vegetable seed system for nutrition project among ethnic minorities in North Vietnam